IMPACT OF ARTERIAL HYPERTENSION AND ENVIRONMENTAL FACTORS ON THE COURSE OF SYSTEMIC LUPUS ERYTHEMATOSUS IN CENTRAL ASIA - Mirzaliyeva A.A; Yunusova M.R.; Sunatullayeva M.E (TADQIQOTLAR, 2026)
Abstract. Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by multisystem involvement and occurs predominantly in women of reproductive age. In Central Asian countries, a high prevalence of arterial hypertension, intense solar radiation, environmental factors, and psychosocial stress may contribute to a more severe course of SLE. The aim of this study was to evaluate the impact of arterial hypertension and other environmental and psychosocial factors on the course of SLE among the population of Central Asia. The study included 120 patients with SLE (110 women and 10 men) aged 18–50 years. The following parameters were assessed: arterial blood pressure, exposure to sunlight, environmental conditions, history of viral infections, and psychosocial stress. The results showed that arterial hypertension, excessive solar radiation, environmental factors, and psychosocial stress exacerbate the course of SLE. Control of these factors may improve disease outcomes.